Highly Mismatched, Dislocation‐Free SiGe/Si Heterostructures. Issue 5 (3rd December 2015) - Isa, Fabio; Salvalaglio, Marco; Dasilva, Yadira Arroyo Rojas; Meduňa, Mojmír; Barget, Michael; Jung, Arik; Kreiliger, Thomas; Isella, Giovanni; Erni, Rolf; Pezzoli, Fabio; Bonera, Emiliano; Niedermann, Philippe; et al.
Abstract : Defect‐free mismatched heterostructures on Si substrates are produced by an innovative strategy. The strain relaxation is engineered to occur elastically rather than plastically by combining suitable substrate patterning and vertical crystal growth with compositional grading. Its validity is proven both experimentally and theoretically for the pivotal case of SiGe/Si(001).